Resveratrol Protects Against Post-Contrast Acute Kidney Injury in Rabbits With Diabetic Nephropathy - Wang, Yongfang; Wang, Bin; Qi, Xun; Zhang, Xin; Ren, Ke (Frontiers in Pharmacology, 2019)
Kidney in diabetic nephropathy state (DN) is more sensitive to post-contrast acute kidney injury (PC-AKI). Resveratrol (Res) is known to a multi-functional polyphenol compound that has protective functions in acute kidney diseases. Here we aimed to examine whether the resveratrol could potentially ameliorate the PC-AKI following DN, and to explore its underlying mechanism in vivo and in vitro. Twenty-four DN rabbits were randomly divided into four groups: control group (Cont), resveratrol group (Res), iohexol group (PC-AKI), and resveratrol plus iohexol group (Res+PC-AKI). All animals underwent MR examinations 24 hours after iohexol injection. Renal histology, blood and urinary biomarkers, silent information regulator l (SIRT1), peroxisome proliferator-activated receptor gamma coactivator-1alpha (PGC-1α), hypoxia-inducible transcription factors-1α (HIF-1α), and apoptosis-associated proteins expression were assessed in ex vivo. For the in vitro experiment, renal tubular epithelial (HK-2) cells, subjected to high glucose condition, were treated with the SIRT1 specific activator resveratrol, SIRT1 specific inhibitor EX527, or HIF-1α specific inhibitor 2-Methoxyestradiol (2-MeOE2) before treatment with iohexol. In the Res+PC-AKI group, the levels of serum creatinine, urea nitrogen, cystatin C and urinary neutrophil gelatinase–associated lipocalin were all decreased; The pure molecular diffusion (D), flow velocity (D*), the fraction of water flowing in capillaries (f) and apparent relaxation rate (R2*) increased, while renal injury score and the apoptosis rate were decreased. Moreover, compared to PC-AKI group, the protein expression levels of SIRT1, PGC-1α and Bal-2 were increased, and the expression levels of HIF-1α, cleaved caspase-3, cytochrome C and Bax were decreased. In addition, iohexol decreased the HK-2 cells survival and increased the cell apoptosis rate; while the results were reversed after treating cells with resveratrol. Furthermore, the SIRTl inhibitors Ex527 reduced the expression of SIRTl, PGC-1α and increased the expression of HIF-1α protein, while the HIF-1α inhibitors 2-MeOE2 was able to reinforce the significant effect of resveratrol. The resveratrol reduces the hypoxia, mitochondrial dysfunction and renal tubular cell apoptosis by activating SIRT1-PGC-1α-HIF-1α signaling pathways in PC-AKI with DN.